(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
As businesses evolve globally, companies are increasingly challenged to stay in a highly competitive market and, as a way to get ahead of their competitors, many employ strategic planning to set their goals and control the achievement of objectives. Regardless of the size of the company, establishing a guide to direct the actions and make sure they remain in line with the intended future objectives is essential. Strategies must be developed to be adopted to stay in the market. Therefore, planning and controlling are necessary functions for all organizations that aspire growth. This work aims to provide a contextualization about strategic planning, its impact on management and decision making, and present the budget as a tool to control plans. A simulated case study presents the implementation of a planning and budget, which proves the efficiency of these tools for management.